The effect of ZIG ZAG training on drilling ability in extracurricular football students, Central Sulawesi - gunawan gunawan gunawan; Hendrik Mentara; Sarpan Sarpan (Kazimierz Wielki University, 2022)
Introduction. The main problem in this research is that there are still types of exercises and basic techniques for dribbling soccer players, causing low dribbling abilities. Objectives of the study. While the purpose of this study, namely to determine the effect of agility on the ability to dribble in soccer extracurricular students in Central Sulawesi. Research methods.. The type of research used is quantitative with a pre-experimental method using a Matching-Only Design design. The sample in this study was taken from the total population of 20 people using the total sampling technique. Furthermore, the samples were separated from the two groups, namely the experimental group (dribbling) with a total of 10 people, and the control group (comparison) with a total of 10 people using the AB-BA formula. Data collection techniques and research instruments using a herding ability test. The data analysis technique in this study uses statistical techniques which include: descriptive analysis, prerequisite test, and research hypothesis testing. Research results andConclusion. Based on the analysis of the results of the research and discussion, it can be concluded that: "There is an effect of agility training on the ability to dribble in soccer extracurricular students in Central Sulawesi". This is evidenced by the value of tcount = 1.91 seconds at df (degrees of freedom) = N - 1 or 10 - 1 = 9, namely the value of ttable = 2.268. So it can be concluded that the value of tcount = 1.91 > t table = 2.268. So it can be concluded that the application of agility training has a significant effect on the ability to dribble in soccer extracurricular students in Central Sulawesi.